The Use of Time Token Method on Students Speaking Ability - Dedi Eryandi Nugraha; Syamsiarna Nappu; Yasser Mallappiang (FKIP Unismuh Makassar, 2023)
The researcher conducted a pre-experimental research with one group Pre-Test, treatment and post-test design. The instrument of this research was speaking test or oral test.This research aimed to find out whether or not the use of the Time Token method effect the eleventh grade students’ speaking ability in terms of smoothness and pronounciation. The sample of this research was class XIIPA2 that consisted of 18 students of SMAN 5 Soppeng. The result showed that Time Token method was effective to effect students’ smoothness (78.33) and pronounciation (73.61) in speaking ability which was proved by the mean score of the Post-Test that was higher than the mean score of the Pre-Test smoothness (42.77) and pronunciation (48.88). Then, there was an effect as many as 83.14% (smoothness) and 50.59% (pronunciation) in describing some topics in three meeting (personal introduction, introduce their family, or explain their favorite place). It means that the student in the speaking class by using Time Token method could affect their speaking ability especially Fluency(smoothness) and pronounciation. However, this only method could not significantly affect the holistic speaking learning activities unless teachers’ use it in their teaching and learning procces.